Clinicopathological profile and outcomes of treatment of head and neck cancer patients in a tertiary care center: a hospital-based prospective study - Puthukudy, Preetham A.; Feshan, Musarrat; Satheesh, Radhika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Globally head and neck cancers constitute among the 10 most common cancers. The study's main purpose was to study the epidemiological and demographic factors and outcomes of treatment of head and neck cancer patients in a tertiary centre. A Chi-square test was used to analyse the association of various factors. Statistical package for the social sciences (SPSS) version 20 was used for statistical analysis. Methods: In this prospective observational study, 52 patients with head and neck cancers were evaluated and data regarding age, gender, risk factors, clinical features, grading, staging, and treatment modality received were taken. Presenting symptoms of patients at the 1st follow-up (at 1 month), 2nd follow-up (at 2 months), and 3rd follow-up (at 6 months) were statistically analysed. Results: Results showed that the mean age group was between 61 to 70 years. Gender distribution showed that 75% were males and 25% were females. The most common site of malignancy was the oropharynx (23.08%). The majority of the tumors were squamous cell carcinoma (88.46%) and are of moderately differentiated type (53.85%). Majority of the tumors (42.31%) presented with stage III lesions. Most of the patients 35 (67.31%) received concurrent chemoradiation (CT-RT). The most common complaint in the first and second follow-up was mucositis. Conclusions: The majority of the tumors are squamous cell carcinoma and are moderately differentiated. Most of the tumors were in stage III, and most received chemoradiation (CT-RT) for treatment.